Evaluation of fast-food consumption by young people in chisinau municipal-ity, Republic of Moldova (One Health & Risk Management, 2021)
Introduction. In recent decades, as the population has become increasingly busy with various chores, many people have begun to eat fast food. At the same time, a research reveals the negative effects of frequent consumption of such foods, especially preferred by young people. In connection with this, we set ourselves the goal of assessing the preferences of young people in Chisinau, Republic of Moldova.Material and methods. It was performed a cross-sectional study using the questionnaire. There were interviewed 100 pupils of the Moldovan-French theoretical high school „Gh. Asachi” and 100 students of the State University of Moldova (68 boys and 132 girls) on the consumption of fast-food products, as well as to determine the level of awareness of the impact of these foods on health. Half of the pupils interviewed were between 12-14 years old, and the other half were between 16-19 years old. The students were between 20 and 24 years old.Results. Out of the total number of respondents, 81% answered that they generally prefer fast food products. At the same time, 48.5% of respondents rarely consumed fast food prepared in specialized units, while 51.5% consumed them with certain regularity. Thus, 5.5% of respondents consumed such foods daily, 8.5% – 2-6 times a week, 8.0% – only once a week, and 29.5% – 1-3 times in the month. The pupils were the ones who used to consume these products more once a week compared to the students, who made up the majority of respondents in the group of those who consume such foods daily and two or more times a week. So, students have proven to be, in general, more faithful consumers. The most frequently consumed products were pizza, being chosen by 72.0% of respondents, followed by fried potatoes, preferred by 60.5% and kebab, the food being chosen by 50.0% of respondents. In descending order after them were preferred: burger, chicken wings and "hot dog". Analyzing the share of fast-food products consumed more often by pupils; it was found that pupils aged 12-14 prefer these products more than those aged 16-19. Students preferred to consume the mentioned foods between 15:00 and 21:00, but pupils - between 12:00 and 18:00. The majority of respondents (60.0%) indicated that the reasons for eating fast food is that they like the taste, but also that they eat with friends or family, 24.5% of respondents consume them for lack of time, 6.5% - because they do not have practical skills in preparing dishes, and 4.5% said that consumption is caused by the fact that they appreciate the variety of these foods. It was revealed, that 26.0% of respondents were not influenced at all by the information in the media about the harmful effect of these foods on the body, while 52% were sometimes influenced, 15% - most of the time and only 7% – of each date. At the same time, 78% of respondents considered fast food in general to be harmful, while 22% consider it beneficial. However, out of the 78% of respondents with negative opinions, only two thirds could name some evil effects.Conclusions. Fast food products were preferred by most of the young people interviewed. Despite the fact that most respondents have heard about the dangers of eating fast food, a third of them cannot name one.
Keywords: fast food; pupils; students.